Ubiquitin-proteasome system-based signature to predict the prognosis and drug sensitivity of hepatocellular carcinoma - Zhang, Jianxiang; Liu, Liwen; Wang, Zenghan; Hou, Mingyang; Dong, Zihui; Yu, Jia; Sun, Ranran; Cui, Guangying (Frontiers in Pharmacology, 2023)
Background: The ubiquitin-proteasome system (UPS) has been implicated in cancer occurrence and progression. Targeting the UPS is emerging as promising therapeutic targets for cancer treatment. Nevertheless, the clinical significance of UPS in hepatocellular carcinoma (HCC) remains incompletely elucidated. Methods: The differentially expressed UPS genes (DEUPS) were screened based on LIHC-TCGA datasets. LASSO and stepwise multivariate regression analysis were conducted to establish UPS-based prognostic risk model. The robustness of this risk model was further validated in HCCDB18, GSE14520, and GSE76427 cohorts. Subsequently, immune features, clinicopathologic characteristics, enrichment pathways and anti-tumor drug sensitivity of the risk model in HCC were further evaluated. Moreover, a nomogram was established to improve prognosis predictive ability of the risk model. Results: Seven UPS-based signatures (ATG10, FBXL7, IPP, MEX3A, SOCS2, TRIM54, and PSMD9) were identified for prognostic risk model establishment. HCC individuals with high risk score present dismal prognosis than those with low risk score. Moreover, larger tumor size, advanced TNM stage and tumor grade were observed in high-risk group. Additionally, cell cycle, ubiquitin mediated proteolysis, and DNA repair pathways were intimately linked to risk score. In addition, obvious immune cell infiltration and sensitive drug response were identified in low-risk patients. Further, both nomogram and risk score showed a powerful prognosis predictive ability. Conclusion: Overall, we established a novel UPS-based prognostic risk model in HCC. Our results will facilitate deep understanding the functional role of UPS-based signature in HCC and provide reliable prediction of clinical outcome and anti-tumor drugs response in HCC patients.